Storage and remobilization of suspended sediment in the lower amazon river of Brazil - Meade, Robert H.; Dunne, Thomas; Richey, Jeffrey E.; Santos, Umberto dos M.; Salati, Eneas (Science, 1985)
In the lower Amazon River, suspended sediment is stored during rising stages of the river and resuspended during falling river stages. The storage and resuspension in the reach are related to the mean slope of the flood wave on the river surface; this slope is smaller during rising river stages than during falling stages. The pattern of storage and resuspension damps out the extreme values of high and low sediment discharge and tends to keep them near the mean value between 3.0 × 106 and 3.5 × 106 metric tons per day. Mean annual discharge of suspended sediment in the lower Amazon is between 1.1 × 109 and 1.3 × 109 metric tons per year.
Keywords: Flood Wave; Lower Amazon; River Stages; Sediment